The unexpected naturalization of Strobilanthes schomburgkii (Craib) J.R.I.Wood (Acanthaceae) in Java, Indonesia - Arifin Surya Dwipa Irsyam; Muhammad Rifqi Hariri; Iin Pertiwi Amin Husaini; Muhammad Hisyam Baidlowi; Ichsan Suwandhi; Dian Rosleine (Check List)
Strobilanthes schomburgkii (Craib) J.R.I.Wood is a plant native to Thailand’s humid tropics. It is discovered to be newly naturalized in Bandung, Cirebon, and Sumedang, West Java. It occurs in riparian habitats along the Winong River and Ciherang River, and in a ditch in Pasir Impun, which resemble its native habitat. The discovery represents the first record of S. schomburgkii as a naturalized species in Indonesia. Considering its recent establishment, regular monitoring and further study of its population dynamics and potential impacts on native vegetation are recommended to anticipate and prevent its possible spread.